2018
DOI: 10.1029/2018ja025426
|View full text |Cite
|
Sign up to set email alerts
|

Saturn's Northern Auroras and Their Modulation by Rotating Current Systems During Late Northern Spring in Early 2014

Abstract: The Hubble Space Telescope imaged Saturn's northern ultraviolet auroras during February–June 2014, when Saturn's northern and southern magnetic perturbation fields were locked in antiphase and matched in rotation period (~10.69 hr). During this coalescence period, we test for evidence of rotational modulation of the auroras using the latest rotating current system model and kilometric radio phases derived from Cassini measurements. While we see modulation of auroral intensity in the rotating frames of the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 84 publications
4
10
1
Order By: Relevance
“…The mean and median UV power distributions (Figure c) are in close agreement between noon and midnight but clearly differ near dawn—the mean maximizing here, while the median minimizes. The mean auroral power agrees very well with intensity averages of previous observations which all showed a distinct peak between 6 and 9 LT (e.g., Bader et al, ; Badman et al, ; Carbary, ; Kinrade et al, ; Lamy et al, , ; Nichols et al, )—but, as seen here, the mean UV intensity/power is obviously not a good representation of the typical state of the aurora. The median directly shows that in more cases than not, the dawn aurora is dimmer than the dusk aurora and not brighter; it is the few transient high‐power events subcorotating through dawn which skew the mean power to unrepresentative high values at these LTs.…”
Section: Typical Auroral Conditions and Periodic Magnetotail Dynamicssupporting
confidence: 88%
See 3 more Smart Citations
“…The mean and median UV power distributions (Figure c) are in close agreement between noon and midnight but clearly differ near dawn—the mean maximizing here, while the median minimizes. The mean auroral power agrees very well with intensity averages of previous observations which all showed a distinct peak between 6 and 9 LT (e.g., Bader et al, ; Badman et al, ; Carbary, ; Kinrade et al, ; Lamy et al, , ; Nichols et al, )—but, as seen here, the mean UV intensity/power is obviously not a good representation of the typical state of the aurora. The median directly shows that in more cases than not, the dawn aurora is dimmer than the dusk aurora and not brighter; it is the few transient high‐power events subcorotating through dawn which skew the mean power to unrepresentative high values at these LTs.…”
Section: Typical Auroral Conditions and Periodic Magnetotail Dynamicssupporting
confidence: 88%
“…A UV power-LT histogram for these images is shown in Figure 2a, with the mean and median power per LT added as line plots; the dawn and dusk slices of this histogram are compared in Figure 2b. We observe similar UV powers through all LTs, disagreeing with previously discussed UV and IR auroral intensity distributions (e.g., Badman et al, 2011;Bader et al, 2018;Carbary, 2012;Kinrade et al, 2018;Lamy et al, 2009Lamy et al, , 2018Nichols et al, 2016) with a brightness peak at dawn probably due to our choice of quiet periods. Centered on roughly 0.5 GW per 40 min LT bin, the powers are more variable and feature a more prominent tail toward lower powers at dawn/noon than at dusk/midnight.…”
Section: Saturn's Quiet Main Aurora: Subcorotational and Ppo Systemscontrasting
confidence: 75%
See 2 more Smart Citations
“…Analyzing HST images from 2007–2008, Nichols et al () found clear evidence of an oscillatory motion of the auroral oval with a period close to the planetary rotation, and Provan et al () showed that the southern oval is generally tilted away from the southern hemisphere's magnetic perturbation field. These findings could be confirmed with 2011–2013 HST data (Nichols et al, ), but not with the 2014 HST data set (Kinrade et al, ). However, many images in the latter data set did not exhibit a dawn arc, preventing reliable circle fits and cutting down the usable data set such that the PPO phase coverage was rather limited.…”
Section: Introductionmentioning
confidence: 86%